Conductive filler, synthesis method thereof and application in polymer materials

By forming polydopamine and silane coupling agents on the surface of carbon nanotubes and loading copper particles, a new type of conductive filler was prepared, which solved the problem of insufficient conductivity of existing ABS materials, significantly improved the conductivity of ABS materials, and had important application significance.

CN119751985APending Publication Date: 2025-04-04HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964256.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing carbon nanotube modified ABS materials cannot meet the performance requirements in some areas where high conductivity performance is required, and it is necessary to develop conductive fillers with better performance to further improve the conductivity of ABS materials.

Method used

A new type of conductive filler is prepared by sequentially forming polydopamine (PDA) and silane coupling agent on the surface of the carbon nanotubes, and then loading copper particles. The conductive filler uses carbon nanotubes as the core. Through the loading of copper particles and the modification of silane coupling agent, the range of conductive paths is increased and the conductive properties of ABS materials are improved.

Benefits of technology

It significantly improves the conductive properties of ABS materials, is of great significance, and can expand the application fields of ABS composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751985A_ABST
    Figure CN119751985A_ABST
Patent Text Reader

Abstract

The present application discloses a conductive filler, a synthesis method thereof and an application in polymer materials. The synthesis method of the conductive filler comprises the following steps: S1, mixing a Tris-HCl buffer solution, dopamine hydrochloride, ammonia water, carbon nanotubes, an alcohol solvent and deionized water, reacting the mixture in a water bath at 50-60° C. for 8-14 hours to obtain a PDA-carbon nanotube material; S2, mixing the PDA-carbon nanotube material with a silane coupling agent, an alcohol solvent and deionized water, reacting the mixture in a water bath at 40-60° C. for 8-10 hours to obtain a silane coupling agent-modified PDA-carbon nanotube material; S3, mixing the silane coupling agent-modified PDA-carbon nanotube material with a soluble copper salt, a reducing agent, an alcohol solvent and deionized water, reacting the mixture in a water bath at 60-70° C. for 8-10 hours to load copper on the silane coupling agent-modified PDA-carbon nanotube material to obtain a conductive filler. The conductive filler has excellent performance and can significantly improve the conductivity of polymer materials, especially ABS materials, compared with simple carbon nanotubes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of filler modification, and specifically relates to a conductive filler and a preparation method thereof, and also relates to the application of the conductive filler in polymer materials. Background Art

[0002] Acrylonitrile Butadiene Styrene (ABS) is a thermoplastic polymer material with high strength, good toughness and easy processing. It is copolymerized by three monomers: acrylonitrile, butadiene and styrene. It has excellent fatigue resistance, heat resistance and dimensional stability. Due to the excellent processing performance of ABS plastic, stable product size, good surface gloss, easy coating and coloring, and excellent comprehensive mechanical properties, it is widely used in the fields of automobiles, electronic appliances, household appliances, etc.

[0003] In some specific applications, ABS is required to have good electrical conductivity. Currently, the improvement of ABS's electrical conductivity is mainly achieved by introducing some fillers with conductive functions into the raw material components, the most common of which is carbon nanotubes (CNTs). Carbon nanotubes are composed of carbon atoms arranged in a hexagonal lattice pattern and rolled into a tubular structure. This structure allows electrons to move freely along the length of the nanotube, making it highly conductive. When added to ABS, it can improve the conductivity of ABS.

[0004] However, at present, for fields with high requirements for conductive properties, simple carbon nanotube-modified ABS materials cannot meet the performance requirements. Therefore, it is necessary to develop conductive fillers with better performance to further improve the conductive properties of ABS materials. Summary of the invention

[0005] In view of this, the primary purpose of the present application is to provide a method for synthesizing a conductive filler. The conductive filler synthesized in the present application has a carbon nanotube as the core, polydopamine (PDA) and a silane coupling agent are sequentially formed on its surface, and then copper particles are loaded. The conductive filler can significantly improve the conductive properties of ABS materials and is of great significance.

[0006] In order to achieve the above objectives, this application adopts the following technical solutions:

[0007] The first aspect of the present application provides a method for synthesizing a conductive filler, comprising the following steps:

[0008] S1, after mixing Tris-HCl buffer solution, dopamine hydrochloride, ammonia water, carbon nanotubes, alcohol solvent and deionized water, reacting in a water bath at 50-60° C. for 8-14 hours to obtain PDA-carbon nanotube material;

[0009] S2, mixing the PDA-carbon nanotube material with a silane coupling agent, an alcohol solvent, and deionized water, and reacting the mixture in a water bath at 40 to 60° C. for 8 to 10 hours to obtain a silane coupling agent-modified PDA-carbon nanotube material;

[0010] S3. Mix the silane coupling agent-modified PDA-carbon nanotube material with a soluble copper salt, a reducing agent, an alcohol solvent, and deionized water, and react in a water bath at 60 to 70° C. for 8 to 10 hours to load copper on the silane coupling agent-modified PDA-carbon nanotube material to obtain a conductive filler.

[0011] In a further embodiment, in step S1, the mass ratio of the Tris-HCl buffer solution, dopamine hydrochloride, ammonia water, carbon nanotubes, alcohol solvent, and deionized water is (30-50): (40-46): (20-30): (30-40): (60-70): (100-120).

[0012] In a further embodiment, in step S2, the mass ratio of the PDA-carbon nanotube material, the silane coupling agent, the alcohol solvent, and the deionized water is (30-40): (10-14): (50-70): (60-90).

[0013] In a further embodiment, in step S3, the mass ratio of the soluble copper salt, the reducing agent, the PDA-carbon nanotube material modified by the silane coupling agent, the alcohol solvent, and the deionized water is (30-36): (0.1-0.3): (50-60): (60-70): (70-90).

[0014] In a further embodiment, the alcohol solvent is ethanol, isopropanol or glycerol.

[0015] In a further embodiment, the silane coupling agent is γ-mercaptopropylmethyldimethoxysilane.

[0016] In a further embodiment, the soluble copper salt is copper nitrate or copper sulfate.

[0017] In a further embodiment, the reducing agent is sodium borohydride.

[0018] A second aspect of the present application provides a conductive filler, which is prepared using the preparation method described above.

[0019] The third aspect of the present application provides the use of the conductive filler as described above in the preparation of polymer materials.

[0020] Preferably, the polymer material is ABS.

[0021] In a fourth aspect, the present application provides a conductive ABS composite material, wherein the raw materials thereof include the conductive filler described above;

[0022] Preferably, the conductive ABS composite material is prepared from the following components in parts by weight:

[0023] 82-102 parts of ABS, 12-16 parts of the conductive filler described above, and 0.1-0.5 parts of an antioxidant;

[0024] Preferably, the antioxidant is one or a mixture of two or more of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.

[0025] A fifth aspect of the present application provides a method for preparing the conductive ABS composite material as described above, comprising the following steps:

[0026] According to the weight ratio, ABS, conductive filler and other remaining components are fully mixed to obtain a uniform mixture;

[0027] The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a conductive ABS composite material.

[0028] In a further embodiment, the twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 200-220°C, zone two temperature 240-260°C, zone three temperature 240-260°C, zone four temperature 240-260°C, zone five temperature 240-260°C, zone six temperature 240-260°C, and head temperature 240-260°C; and / or, screw speed 200-280r / min.

[0029] Beneficial effects of this application:

[0030] (1) The present application first synthesizes a PDA-carbon nanotube material, then introduces a thiol group into the PDA-carbon nanotube material through silane coupling agent modification to obtain a silane coupling agent-modified PDA-carbon nanotube material, and finally obtains copper through an oxidation-reduction reaction and allows it to be loaded on the silane coupling agent-modified PDA-carbon nanotube material. The structure is as follows: Figure 1 As shown in .

[0031] The present application uses carbon nanotubes to construct a conductive channel and copper particles to fill the gap to increase the range of the conductive path. This is achieved by mixing and complementing each other through the morphological differences between the filler particles, which can better reduce the gaps between the conductive particles and is conducive to the formation of conductive chains, thereby improving ABS and enhancing the conductive properties of ABS.

[0032] (2) The mercapto group contained in the silane coupling agent can form a stable copper-sulfur complex on the copper surface on the one hand, and on the other hand, it can react with the catechol group of PDA to serve as a bridge connecting copper and carbon nanotubes.

[0033] (3) This application synthesizes a new type of functional conductive filler, which can improve the conductivity of ABS and has great promotion significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the structure of the conductive filler synthesized in this application. DETAILED DESCRIPTION

[0035] The following will clearly and completely describe the implementation methods of the present application. The technical solutions in the implementation methods described below are exemplary and are only possible technical implementations of the present application, not all possible implementations. Those skilled in the art can fully combine the implementation methods of the present application to obtain other implementation methods without creative work, and these implementation methods are also within the scope of protection of the present application.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0037] In addition, unless otherwise specified, methods without specific description of conditions or steps are conventional methods, and the reagents and materials used are all commercially available.

[0038] The raw materials used in the following examples are as follows:

[0039] ABS (model 750A), Daqing Petrochemical; dopamine hydrochloride, Shanghai Yushao Biotechnology Co., Ltd.; Tris-HCl buffer solution, Hubei Xindesheng Material Technology Co., Ltd.; ammonia water, Jinan Mingchuan Chemical Co., Ltd.; ethanol, Shandong Taixi Chemical Co., Ltd.; carbon nanotubes, Dongguan Yushuo New Materials Co., Ltd.; γ-mercaptopropylmethyldimethoxysilane, Shandong Xiya Chemical Co., Ltd.; sodium borohydride, Zhongshan Dixin Chemical Co., Ltd.; copper nitrate, Shandong Xinhongrui Chemical Co., Ltd.; deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.; antioxidants (models Irganox168, Irganox1010, Irganox1330), BASF.

[0040] Example 1

[0041] This embodiment provides a method for synthesizing a conductive filler, and the specific steps are as follows:

[0042] (1) 300 g of Tris-HCl buffer solution, 400 g of dopamine hydrochloride, 200 g of ammonia water, 300 g of carbon nanotubes, 600 g of ethanol, and 1.0 kg of deionized water were mixed in a flask, reacted in a 50° C. water bath for 8 h, filtered and washed, and dried in a 50° C. oven for 4 h to obtain PDA-carbon nanotube material.

[0043] (2) 300 g of PDA-carbon nanotube material, 100 g of γ-mercaptopropylmethyldimethoxysilane, 500 g of ethanol, and 600 g of deionized water were mixed and placed in a flask, reacted in a 40°C water bath for 8 h, filtered and washed, and dried in a 60°C oven for 8 h to obtain a γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material.

[0044] (3) 300 g of copper nitrate, 1 g of reducing agent sodium borohydride, 500 g of γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material, 600 g of ethanol, and 700 g of deionized water were mixed and placed in a flask, reacted in a 60°C water bath for 8 h, filtered and washed, and dried in an oven at 60°C for 6 h. Copper was loaded on the γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material, which was recorded as conductive filler M1.

[0045] Application Example 1

[0046] The conductive filler M1 prepared in Example 1 is used to prepare a conductive ABS composite material, and the specific steps are as follows:

[0047] (1) According to weight parts, 82 parts of ABS, 12 parts of conductive filler M1, and 0.1 parts of Irganox 1010 were weighed, mixed, and stirred to obtain a mixture;

[0048] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a conductive ABS composite material, which is denoted as P1;

[0049] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 200°C, zone two temperature 240°C, zone three temperature 240°C, zone four temperature 240°C, zone five temperature 240°C, zone six temperature 240°C, head temperature 240°C, and screw speed 200r / min.

[0050] Example 2

[0051] This embodiment provides a method for synthesizing a conductive filler, and the specific steps are as follows:

[0052] (1) 500 g of Tris-HCl buffer solution, 460 g of dopamine hydrochloride, 300 g of ammonia water, 400 g of carbon nanotubes, 700 g of ethanol, and 1.2 kg of deionized water were mixed in a flask, reacted in a 60° C. water bath for 14 h, filtered and washed, and dried in a 70° C. oven for 6 h to obtain a PDA-carbon nanotube material.

[0053] (2) 400 g of PDA-carbon nanotube material, 140 g of γ-mercaptopropylmethyldimethoxysilane, 700 g of ethanol, and 900 g of deionized water were mixed and placed in a flask, reacted in a 60° C. water bath for 10 h, filtered and washed, and dried in an oven at 70° C. for 10 h to obtain a γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material.

[0054] (3) 360 g of copper nitrate, 3 g of reducing agent sodium borohydride, 600 g of PDA-carbon nanotube material modified with γ-mercaptopropylmethyldimethoxysilane, 700 g of ethanol, and 900 g of deionized water were mixed and placed in a flask, reacted in a 70°C water bath for 10 h, filtered and washed, and dried in an oven at 80°C for 8 h. Copper was loaded on the PDA-carbon nanotube material modified with γ-mercaptopropylmethyldimethoxysilane, which was recorded as conductive filler M2.

[0055] Application Example 2

[0056] The conductive filler M2 prepared in Example 2 is used to prepare a conductive ABS composite material, and the specific steps are as follows:

[0057] (1) 102 parts of ABS, 16 parts of conductive filler M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330 were weighed and mixed and stirred to obtain a mixture;

[0058] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a conductive ABS composite material, which is denoted as P2;

[0059] The twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of the zones are: zone 1 temperature 220°C, zone 2 temperature 260°C, zone 3 temperature 260°C, zone 4 temperature 260°C, zone 5 temperature 260°C, zone 6 temperature 260°C, and die head temperature 260°C. The screw speed is 280r / min.

[0060] Example 3

[0061] This embodiment provides a method for synthesizing a conductive filler, and the specific steps are as follows:

[0062] (1) 400 g of Tris-HCl buffer solution, 430 g of dopamine hydrochloride, 250 g of ammonia water, 350 g of carbon nanotubes, 650 g of ethanol, and 1.1 kg of deionized water were mixed in a flask, reacted in a 55° C. water bath for 11 h, filtered and washed, and dried in an oven at 60° C. for 5 h to obtain a PDA-carbon nanotube material.

[0063] (2) 350 g of PDA-carbon nanotube material, 120 g of γ-mercaptopropylmethyldimethoxysilane, 600 g of ethanol, and 750 g of deionized water were mixed and placed in a flask, reacted in a 50° C. water bath for 9 h, filtered and washed, and dried in a 65° C. oven for 9 h to obtain a γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material.

[0064] (3) 330 g of copper nitrate, 2 g of reducing agent sodium borohydride, 550 g of γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material, 650 g of ethanol, and 800 g of deionized water were mixed and placed in a flask, reacted in a 65°C water bath for 9 h, filtered and washed, and dried in an oven at 70°C for 7 h. Copper was loaded on the γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material, which was recorded as conductive filler M3.

[0065] Application Example 3

[0066] The conductive filler M3 prepared in Example 3 is used to prepare a conductive ABS composite material, and the specific steps are as follows:

[0067] (1) According to weight parts, 92 parts of ABS, 14 parts of conductive filler M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010 were weighed, mixed and stirred to obtain a mixture;

[0068] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a conductive ABS composite material, which is denoted as P3;

[0069] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 215°C, zone two temperature 255°C, zone three temperature 255°C, zone four temperature 255°C, zone five temperature 255°C, zone six temperature 255°C, head temperature 255°C, and screw speed 245r / min.

[0070] Example 4

[0071] This embodiment provides a method for synthesizing a conductive filler, and the specific steps are as follows:

[0072] (1) 335 g of Tris-HCl buffer solution, 425 g of dopamine hydrochloride, 255 g of ammonia water, 365 g of carbon nanotubes, 625 g of ethanol, and 1.05 kg of deionized water were mixed in a flask, reacted in a 58° C. water bath for 12 h, filtered and washed, and dried in an oven at 68° C. for 4 h to obtain a PDA-carbon nanotube material.

[0073] (2) 395 g of PDA-carbon nanotube material, 135 g of γ-mercaptopropylmethyldimethoxysilane, 615 g of ethanol, and 725 g of deionized water were mixed and placed in a flask, reacted in a 58°C water bath for 9.5 h, filtered and washed, and dried in an oven at 68°C for 8.5 h to obtain a γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material.

[0074] (3) 355 g of copper nitrate, 2.5 g of reducing agent sodium borohydride, 555 g of γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material, 635 g of ethanol, and 735 g of deionized water were mixed and placed in a flask, reacted in a 66°C water bath for 8.3 h, filtered and washed, and dried in an oven at 75°C for 6.5 h. Copper was loaded on the γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material, which was recorded as conductive filler M4.

[0075] Application Example 4

[0076] The conductive filler M4 prepared in Example 4 is used to prepare a conductive ABS composite material, and the specific steps are as follows:

[0077] (1) According to weight parts, 85 parts of ABS, 14.5 parts of conductive filler M4, 0.1 parts of antioxidant Irganox1010, and 0.2 parts of antioxidant Irganox1330 were weighed, mixed and stirred to obtain a mixture;

[0078] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a conductive ABS composite material, which is denoted as P4;

[0079] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 215°C, zone two temperature 245°C, zone three temperature 245°C, zone four temperature 245°C, zone five temperature 245°C, zone six temperature 245°C, head temperature 245°C, and screw speed 245r / min.

[0080] Example 5

[0081] This embodiment provides a method for synthesizing a conductive filler, and the specific steps are as follows:

[0082] (1) 333 g of Tris-HCl buffer solution, 455 g of dopamine hydrochloride, 285 g of ammonia water, 366 g of carbon nanotubes, 675 g of ethanol, and 1.15 kg of deionized water were mixed in a flask, reacted in a 59° C. water bath for 13 h, filtered and washed, and dried in an oven at 61° C. for 5 h to obtain a PDA-carbon nanotube material.

[0083] (2) 315 g of PDA-carbon nanotube material, 125 g of γ-mercaptopropylmethyldimethoxysilane, 545 g of ethanol, and 655 g of deionized water were mixed and placed in a flask, reacted in a 52° C. water bath for 9.5 h, filtered and washed, and dried in a 62° C. oven for 8.6 h to obtain a γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material.

[0084] (3) 335 g of copper nitrate, 2.5 g of reducing agent sodium borohydride, 585 g of γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material, 696 g of ethanol, and 735 g of deionized water were mixed and placed in a flask, reacted in a 67°C water bath for 9.5 h, filtered and washed, and dried in an oven at 78°C for 6 h. Copper was loaded on the γ-mercaptopropylmethyldimethoxysilane-modified PDA-carbon nanotube material, which was recorded as conductive filler M5.

[0085] Application Example 5

[0086] The conductive filler M5 prepared in Example 5 is used to prepare a conductive ABS composite material, and the specific steps are as follows:

[0087] (1) According to weight parts, 95 parts of ABS, 15.5 parts of conductive filler M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168 were weighed, mixed, and stirred to obtain a mixture;

[0088] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a conductive ABS composite material, which is denoted as P5;

[0089] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 215°C, zone two temperature 255°C, zone three temperature 255°C, zone four temperature 255°C, zone five temperature 255°C, zone six temperature 255°C, head temperature 255°C, and screw speed 255r / min.

[0090] In order to reflect the technical advantages of the conductive filler of the present application, the present application uses Application Example 5 as a reference and conducts the following comparative examples:

[0091] Comparative Example 1

[0092] This comparative example discloses another method for preparing a conductive ABS composite material, and the specific steps are as follows:

[0093] (1) According to weight parts, 95 parts of ABS, 15.5 parts of carbon nanotubes, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168 were weighed, mixed, and stirred to obtain a mixture;

[0094] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a conductive ABS composite material, which is denoted as D1;

[0095] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 215°C, zone two temperature 255°C, zone three temperature 255°C, zone four temperature 255°C, zone five temperature 255°C, zone six temperature 255°C, head temperature 255°C, and screw speed 255r / min.

[0096] Comparative Example 2

[0097] This comparative example discloses another method for preparing a conductive ABS composite material, and the specific steps are as follows:

[0098] (1) According to weight parts, 95 parts of ABS, 15.5 parts of copper powder, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168 were weighed, mixed, and stirred to obtain a mixture;

[0099] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a conductive ABS composite material, which is denoted as D1;

[0100] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 215°C, zone two temperature 255°C, zone three temperature 255°C, zone four temperature 255°C, zone five temperature 255°C, zone six temperature 255°C, head temperature 255°C, and screw speed 255r / min.

[0101] Comparative Example 3

[0102] This comparative example discloses another method for preparing a conductive ABS composite material, and the specific steps are as follows:

[0103] (1) According to weight parts, 95 parts of ABS, 12.5 parts of carbon nanotubes, 3 parts of copper powder, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168 were weighed, mixed and stirred to obtain a mixture;

[0104] (2) extruding the mixture obtained in step (1) through a twin-screw extruder to form granules to obtain a conductive ABS composite material, which is denoted as D1;

[0105] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 215°C, zone two temperature 255°C, zone three temperature 255°C, zone four temperature 255°C, zone five temperature 255°C, zone six temperature 255°C, head temperature 255°C, and screw speed 255r / min.

[0106] Performance Testing

[0107] The conductive ABS composite materials prepared in Application Examples 1-5 and Comparative Examples 1-3 were respectively injection molded into discs with a diameter of 80 mm and a thickness of 30 mm, and the surface resistivity was tested. The specific test method was referred to GBT 31838.3-2019, and the results are shown in Table 1.

[0108] Table 1 Test results of conductive ABS composite materials performance

[0109]

[0110]

[0111] It can be seen from the test results in Table 1 that the conductive properties of the ABS composite materials of Application Examples 1-5 are better than those of Comparative Examples 1-3, which is mainly due to the preparation of the conductive filler in the present application. This shows that the conductive filler synthesized in the present application has excellent conductivity, which can give the ABS composite material more outstanding conductive properties, thereby expanding the application field of the ABS composite material.

[0112] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for synthesizing a conductive filler, characterized in that: The following steps are involved: S1, after mixing Tris-HCl buffer solution, dopamine hydrochloride, ammonia water, carbon nanotubes, alcohol solvent and deionized water, reacting in a water bath at 50-60° C. for 8-14 hours to obtain PDA-carbon nanotube material; S2, mixing the PDA-carbon nanotube material with a silane coupling agent, an alcohol solvent, and deionized water, and reacting the mixture in a water bath at 40 to 60° C. for 8 to 10 hours to obtain a silane coupling agent-modified PDA-carbon nanotube material; S3, mixing the silane coupling agent-modified PDA-carbon nanotube material with a soluble copper salt, a reducing agent, an alcohol solvent, and deionized water, and reacting the mixture in a water bath at 60 to 70° C. for 8 to 10 hours, and loading copper on the silane coupling agent-modified PDA-carbon nanotube material to obtain a conductive filler; Preferably, in step S1, the mass ratio of the Tris-HCl buffer solution, dopamine hydrochloride, ammonia water, carbon nanotubes, alcohol solvent, and deionized water is (30-50): (40-46): (20-30): (30-40): (60-70): (100-120); Preferably, in step S2, the mass ratio of the PDA-carbon nanotube material, the silane coupling agent, the alcohol solvent, and the deionized water is (30-40): (10-14): (50-70): (60-90); Preferably, in step S3, the mass ratio of the soluble copper salt, the reducing agent, the PDA-carbon nanotube material modified by the silane coupling agent, the alcohol solvent, and the deionized water is (30-36): (0.1-0.3): (50-60): (60-70): (70-90).

2. The method for synthesizing a conductive filler according to claim 1, wherein: The alcohol solvent is ethanol, isopropanol or glycerol.

3. The method for synthesizing a conductive filler according to claim 1, wherein: The silane coupling agent is γ-mercaptopropylmethyldimethoxysilane.

4. The method for synthesizing a conductive filler according to claim 1, wherein: The soluble copper salt is copper nitrate or copper sulfate.

5. The method for synthesizing a conductive filler according to claim 1, wherein: The reducing agent is sodium borohydride.

6. A conductive filler, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the conductive filler as claimed in claim 6 in the preparation of polymer materials; Preferably, the polymer material is ABS.

8. A conductive ABS composite material, characterized in that: The raw materials include the conductive filler as claimed in claim 6; Preferably, the conductive ABS composite material is prepared from the following components in parts by weight: 82-102 parts of ABS, 12-16 parts of the conductive filler according to claim 6 and 0.1-0.5 parts of an antioxidant; Preferably, the antioxidant is one or a mixture of two or more of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.

9. A method for preparing the conductive ABS composite material as claimed in claim 8, characterized in that: The following steps are involved: According to the weight ratio, ABS, conductive filler and other remaining components are fully mixed to obtain a uniform mixture; The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a conductive ABS composite material.

10. The preparation method according to claim 9, characterized in that: The twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 200-220°C, zone two temperature 240-260°C, zone three temperature 240-260°C, zone four temperature 240-260°C, zone five temperature 240-260°C, zone six temperature 240-260°C, die head temperature 240-260°C; and / or, screw speed 200-280r / min.